1987
DOI: 10.1007/bf00606637
|View full text |Cite
|
Sign up to set email alerts
|

The effects of obesity and exercise on the pharmacokinetics of caffeine in lean and obese volunteers

Abstract: The effects of obesity, exercise, and the interaction of obesity and exercise were examined in 6 caffeine naive, untrained, nonsmoking, college males (3 lean (LV), 3 obese (OV]. Each subject received caffeine (oral, 5.83 mg X kg-1 lean body weight) or placebo (50 mg citrate) prior to 3 h of seated rest and prior to 90 min of treadmill walking (40% of their maximal aerobic power) followed by 90 min of seated recovery. Serum samples were collected at various times and analyzed for caffeine by HPLC. Pharmacokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…This demonstrates an impairment of the final degradetion of dimethylxanthines into monomethylxanthines, the end products of caffeine metabolism. These results agree with those in the study of Kamimori et al [52], which described a longer half-life and a slower elimination rate constant for caffeine in obese subjects.…”
Section: Caffeine and Energy Expendituresupporting
confidence: 93%
See 2 more Smart Citations
“…This demonstrates an impairment of the final degradetion of dimethylxanthines into monomethylxanthines, the end products of caffeine metabolism. These results agree with those in the study of Kamimori et al [52], which described a longer half-life and a slower elimination rate constant for caffeine in obese subjects.…”
Section: Caffeine and Energy Expendituresupporting
confidence: 93%
“…The pharmacokinetics of caffeine is different in lean and obese subjects [7,[51][52][53]. It was found that caffeine amplifies fat oxidation better in lean vs. obese women [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Males were recruited, as the use of oral contraceptives can augment the half-life of caffeine [19], and throughout the luteal phase of the menstrual cycle caffeine clearance can be reduced [20]. Subjects were non-smokers, as nicotine can adjust the rate of caffeine degradation [21]. Subjects with a low caffeine intake were recruited as it was shown that chronic consumption can result in the up regulation of adenosine receptors and therefore reduce caffeine's acute effects [22].…”
Section: Subjectsmentioning
confidence: 99%
“…Participants (N = 16) were nonsmoking college-age women of average body weight who reported low to moderate daily caffeine consumption (i.e., ≤200 mg/day) and no hypersensitivity to caffeine. Only nonsmokers of average body weight (i.e., BMI ≤25) were recruited to avoid the effects of cigarette smoking (Joeres et al, 1988) and obesity (Kamimori, Somani, Knowlton, & Perkins, 1987) on the rate of caffeine metabolism. Participants who reported low to moderate daily caffeine consumption were recruited to minimize tolerance of the effects of caffeine among habitual consumers of caffeine (Laska et al, 1984).…”
Section: Participantsmentioning
confidence: 99%